VD_FINDINFO HC / 2011 / 547 vom 14. September 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, CONJOINT, PROTECTION DE L'UNION CONJUGALE | 163 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH)